1998
DOI: 10.1055/s-1998-2042
|View full text |Cite
|
Sign up to set email alerts
|

Phenylboronic Acid-Mediated Synthesis of 2H-Chromenes

Abstract: Condensation of phenols with but-2-enal and 3-methylbut-2-enal in the presence of phenylboronic acid in acetic acid-toluene solution leads to substituted and condensed 2H-chromenes, constituting a mild and advantageous complement to classical routes for this class of heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 10 publications
3
34
0
1
Order By: Relevance
“…The bicyclic ring system of chromenes, like coumarin, has inspired a number of different synthetic approaches [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bicyclic ring system of chromenes, like coumarin, has inspired a number of different synthetic approaches [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors point out that when coumarin is treated with ethanolic sodium ethoxide at reflux, the lactone ring is opened (Scheme 3) to give 2-(ethylpropenoate)-phenoxide (5). Subsequent treatment of (5) with water and evaporation of the solvent brought about saponification of the ester and, with careful acidification, produces ocoumaric acid [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that phenylboronic acid (PhB(OH) 2 ) is useful for benzopyran synthesis. 14,15) At first, we prepared precocene I and II by the reaction of methoxyphenols with 3-methyl-2-butenal using PhB(OH) 2 in acidic conditions. In addition, the dipyran analogues including natural products octandrenolone, clusiaphenone A, and relatives were prepared.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, this reaction also take place between phenols and , -unsaturated aldehydes under acid conditions. [27,28] Condensation between salicylaldehydes and unsaturated esters followed by a subsequent decarboxylation was also used [29][30][31] as well as oxidative cyclization of 2-allylphenols [32,33]. The present work illustrates the versatility of ytterbium triflate and its usefulness in improving the synthetic method mentioned above [3], which required the use of a pressure reactor and heating, into a room temperature experiment only requiring a stoppered glass tube.…”
mentioning
confidence: 88%